The development of the notion of "event" in Józef Bańka’s quantum recentivism - Chojnacka, Justyna (Folia Philosophica, 2003)
The present article is an introduction into the most recent philosophical stance taken by Józef Bańka, i.e. his quantum recentivism presented in his book, Our Father Who Are Now. This stance corresponds to the research conducted by contemporary scientists, and consisting in attempts at arrive at “general theory of everything.” Such a theory would be capable of explaining the ideas of pure presentness and the philosophy of presentness, and it would also explain what the cause for rise of the universe and its continued existence was. The quantum recentivism is a stance allowing us to solve the above problems on the basis of philosophy, and the transcendental ontology introduced there creates new possibilities for the system. Thus, the essential idea is that of “event” (the Absolute), which has changed the range it used to have. From now on, its ontological area is both the anthropic Self of the infant recential, and the Supermonad of the parallel recential. Owing to a transcendental “recoupling” between the two areas there takes place the relation described as “event - collision” (zdarzenie - zderzenie). The aim of the present article is then to discuss the development of the notion of “event” in quantum recentivism, and to emphasise its originality as the quantum theory constitutes a novelty for recentivist philosophy. In view of this fact, a new terminology has to be applied, and this matter has also been discussed here while presenting the theory.